From abolition of the slave trade to protection of immigrants: Danish colonialism, German missionaries, and the development of ideas of humanitarian governance from the early eighteenth to the nineteenth century. Issue 3 (2nd July 2020) - Kaarsholm, Preben
ABSTRACT: The focus of the essay is the emergence in the eighteenth century of discourses of abolition in the context of bonded labour and the trade in slaves from India. It relates this to the development in forms of unfree labour from slavery to indenture, and to the travels of abolitionism from the Indian Ocean world into that of the Atlantic. The study examines multinational dimensions of this early history of abolition and discusses more particularly how missionary enterprises based in Danish colonies in India contributed to the development of ideas of education, enlightenment, and natural rights that fed into emerging discourses of abolitionism. Further, the essay links eighteenth-century debates around abolition to discourses of protection and humanitarianism that became prominent in the last half of the nineteenth century in the context of imperialist competition and campaigns against the illegal slave trade.